Analysis Of Fetal Growth Restriction in Pregnancy - V, Sangeetha; B M, Logeswari; P, Niveditha (Journal of Neonatal Surgery, 2025)
Context/Background: Fetal Growth Restriction (FGR) is a pressing challenge in obstetrics, where a baby does not reach its full genetic growth potential in the womb. Globally, FGR affects 10-15% of pregnancies and is linked to serious complications such as preterm births, low birth weight, and the need for neonatal intensive care. This study sheds light on how common FGR is, what factors contribute to it, and its impact on newborn health, aiming to better inform care for mothers and their babies. Aims/Objectives: Aim of this study is to understand the Fetal Growth Restriction: Its Prevalence, Risk Factors, and Impact on Neonatal Health To explore how often FGR occurs, uncover the maternal, fetal, and placental factors that increase its risk, and examine the effects of FGR on newborn health outcomes in a hospital setting. Methodology: This study was conducted at the Obstetrics and Gynecology Department of Sree Balaji Medical College and Hospital, Chennai. It included 100 pregnant women who were either suspected or confirmed to have FGR. Only women with single pregnancies above 18 years of age were included, while pregnancies with fetal anomalies or multiple babies were excluded. We collected detailed information on the mothers' health, pregnancy history, and ultrasound findings. Fetal growth and placental health were monitored using ultrasonography and Doppler studies. Newborn outcomes like birth weight, gestational age, and NICU admissions were analyzed, with statistical significance set at p-values <0.05. Results: FGR was most common among mothers aged 26-30 years (44%), with first-time mothers (primigravida) being more likely to experience FGR (68%, p = 0.003). Maternal conditions like hypertension (20%, p < 0.001), anemia (24%), and diabetes (12%) significantly increased the risk of FGR. Babies born with FGR were more likely to have low birth weights (68% weighed ≤2.5 kg, p = 0.001) and be born preterm (70%, p < 0.001). Delivery via cesarean section was higher among FGR cases (64%, p = 0.007). Additionally, 40% of FGR babies required NICU care, and 16% experienced respiratory distress—both significantly higher compared to babies without FGR. Conclusions: FGR is closely linked to maternal health issues like hypertension, anemia, and diabetes, and leads to challenging neonatal outcomes, including low birth weight, preterm births, and NICU admissions. Early detection and proactive management, including regular prenatal monitoring and personalized care, are critical to reducing the risks associated with FGR. These findings emphasize the importance of comprehensive care plans that address maternal health to improve outcomes for both mothers and their babies.